GENETIC VARIATION OF Tor tambroides (Bleeker, 1854) ALONG BATANG TARUSAN RIVER, WEST SUMATERA: IMPLICATIONS FOR STOCK IDENTIFICATION - Arif Wibowo; Siswanta Kaban (Indonesian Fisheries Research Journal, 2015)
Mahseer (Tor tambroides, Bleeker, 1854) is an important consumption fish species in the Batang Tarusan River, located in the West Sumatera, Indonesia. In this study the CO1 of mtDNA sequence data were used to investigate genetic variability within and between populations of mahseer. Twenty four tissue samples were collected for genetic analysis in the Batang Tarusan River. Genetic analysis revealed two different haplotypes were existed. The overall nucleotide and haplotype variability were low in all sampling sites. Hierarchical AMOVA analysis showed that mahseer populations form a single panmictic population with low FST= 0.02794; p = 0.418 and high gene flow among population sampling. Corroborated result by genetic analysis; there is a strong argument suggesting that the populations could be treated as a single stock unit.